Sosialisasi Digital Marketing UMKM Guna Meningkatkan Perekonomian Masyarakat Kelurahan Laweyan Surakarta - Prihadi, Singgih; Ardiyana, Sasna Syifa; Ardhana, Bima Kusuma; Iqbal, Muhammad; Dewi, Nadya Putri; Pradwita, Yanuarizka Widhi; Fauziyah, Riska Annisa; Pertiwi, Ratu Seffy; Fadilah, Nur; Annafi, Rizka; Ghaniyasari, Nur Azizah (Edumedia Solution, 2023)
This MSME digital marketing socialization activity aims to provide an understanding of digital marketing in an effort to increase sales of MSME products in Laweyan Village. Socialization activities were carried out using observation, interviews, lectures and discussions with the target of the activities being MSME actors in Laweyan Village. It is hoped that MSME digital marketing outreach activities will be useful and implemented by MSME players so that they can improve the economy of the Laweyan Village.